A review on electrospun nanofibers for multiple biomedical applications. (2nd November 2022) - Patel, Pratikshkumar R.; Gundloori, Rathna Venkata Naga
Abstract: Electrospinning is a well‐known technique since 1544 to fabricate nanofibers using different materials like polymers, metals oxides, proteins, and many more. In recent years, electrospinning has become the most popular technique for manufacturing nanofibers due to its ease of use and economic viability. Nanofibers have remarkable properties like high surface‐to‐volume ratio, variable pore size distribution (10–100 nm), high porosity, low density, and are suitable for surface functionalization. Therefore, electrospun nanofibers have been utilized for numerous applications in the pharmaceutical and biomedical field like tissue engineering, scaffolds, grafts, drug delivery, and so on. In this review article, we will be focusing on the versatility, current scenario, and future endeavors of electrospun nanofibers for various biomedical applications. This review discusses the properties of nanofibers, the background of the electrospinning technique, and its emergence in chronological order. It also covers the various types of electrospinning methods and their mechanism, further elaborating the factors affecting the properties of nanofibers, and applications in tissue engineering, drug delivery, nanofibers as biosensor, skin cancer treatment, and magnetic nanofibers.